PENDUGAAN SURPLUS AIR TANAH MENGGUNAKAN MODEL NERACA AIR (STUDI KASUS SUB DAERAH ALIRAN SUNGAI CICATIH)ESTIMATES OF SOIL MOISTURE SURPLUS USING WATER BALANCE MODEL IN CICATIH WATERSHED - S. Kurnianto; D. Murdiyarso (Agromet, 2004)
Abstract is available in the full text (pdf format)